Mirabegron in the Management of Overactive Bladder Syndrome - O'Kane M; Robinson D; Cardozo L; Wagg A; Abrams P (Dove Medical Press, 2022)
Miriam O'Kane,1 Dudley Robinson,1 Linda Cardozo,1 Adrian Wagg,2 Paul Abrams3 1Department of Urogynaecology, King's College Hospital, London, UK; 2Department of Medicine, University of Alberta, Edmonton, Alberta, Canada; 3Bristol Urological Institute, Bristol, UKCorrespondence: Dudley Robinson, Department of Urogynaecology, King's College Hospital, London, SE5 9RS, UK, Tel +44 203 299 3568, Fax +44 203 299 3449, Email dudley.robinson@nhs.netAbstract: Overactive bladder (OAB) negatively affects work productivity and quality of life in sufferers. Its overall impact is likely to increase as a result of increasing prevalence in an ageing population. The pathophysiology of OAB is not completely understood but the β 3-adrenoceptor, which is highly expressed in the urinary bladder, is thought to be important for mediating human detrusor relaxation during the storage phase. Clinical trial results have demonstrated that mirabegron, a selective β 3-adrenoceptor agonist offers substantial clinical efficacy and good adherence rates over 12 months. Furthermore, due to its different mechanism of action, it is likely to offer a favourable tolerability profile when compared with antimuscarinic agents, resulting in improved persistence over long-term treatment. Finally, from a health economic perspective, despite its higher drug acquisition cost, mirabegron has been found to be cost-effective, owing to the greater increase in quality-adjusted-life-years gained, when compared to antimuscarinic medications. The PubMed database was searched for English language articles published between 1 January 2005 to 31 January 2022, on the subject of mirabegron. Search terms included "mirabegron", "overactive bladder", "β 3-adrenoceptor agonist", "urinary incontinence". This review summarises the evidence for mirabegron as a treatment option for the management of OAB.Keywords: β 3-adrenoceptor agonist, drug therapy, mirabegron, overactive bladder, urinary incontinence